Antitumor effects of natural killer cells derived from gene-engineered human-induced pluripotent stem cells on hepatocellular carcinoma - Mayuna Nakamura; Yuka Tanaka; Keishi Hakoda; Masahiro Ohira; Tsuyoshi Kobayashi; Kenji Kurachi; Kouichi Tamura; Hideki Ohdan (Cancer Immunology, Immunotherapy)
Abstract Mortality and recurrence rates of hepatocellular carcinoma (HCC) remain high despite the use of various treatment methods. Recently, cell-based immunotherapy using natural killer (NK) cells has attracted considerable attention in cancer immunotherapy. NK cells generated from induced pluripotent stem cells (iPSCs) are a new option for use as an NK cell resource. The eNK cells (HLCN061, developed by HEALIOS K.K.) are human iPSC-derived NK cells differentiated from clinical-grade iPSCs in which IL-15, CCR2B, CCL19, CD16a, and NKG2D have been introduced. In this study, we aimed to evaluate the potential of eNK cell therapy for HCC treatment. The analysis of eNK cells for cell surface and intracellular molecules revealed that antitumor-related surface molecules (TRAIL, CD226, and CD16) and intracellular cytotoxic factors (perforin, granzyme B, TNFα, and IFNγ) were highly expressed. In addition, eNK cells exhibited high cytotoxicity against HCC cell lines (HepG2, HuH7, and SNU-423), which are sensitive to NKG2D, TRAIL, and CD226. The TRAIL and perforin/granzyme B pathways are largely involved in this cytotoxic mechanism, as indicated by the reduction in cytotoxicity induced by TRAIL inhibitory antibodies and concanamycin A, which inhibits perforin/granzyme B-mediated cytotoxicity. Our data suggest that eNK cells, whose functions have been enhanced by genetic engineering, have the potential to improve HCC treatment.